Sosialisasi Perawatan Sepeda Motor di Desa Sibuntuon Kecamatan Dolok Pardamean Kabupaten Simalungun Provinsi Sumatera Utara: Penelitian - Putra Samuel Manihuruk; Surya Seftian Sidabalok; Christophe Jestius Sipayung; Jose Mikael Saragih; Tambos August Sianturi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to Socialize Motorcycle Maintenance in Sibuntuon Village, Dolok Pardamean District, Simalungun Regency, North Sumatra Province. From the Community Service Lecture activity where the implementation of the 2021 KPPM program of HKBP Nommensen University, Pematangsiantar in Sibuntuon Village, Dolok Pardamean District, Simalungun Regency, the conclusions obtained include: 1) Through motorcycle maintenance socialization activities, it is hoped that it can provide insight into the importance of caring for and maintaining the performance of their motorbikes 2) Through motorcycle maintenance socialization activities and with good education, motorbike owners can avoid unnecessary damage, as well as extend the life of the vehicle and also ensure safety while driving. First of all, the author would like to express his deepest gratitude to the Institute for Research and Community Service (LPPM) of HKBP Nommensen University, Pematangsiantar for providing the opportunity to carry out this activity. Furthermore, my gratitude is also conveyed to the Head of Sibuntuon Village, Dolok Pardamean District, Simalungun Regency who has permitted the participants of the KPPM of HKBP Nommensen Pematangsiantar University for the February-March Period in Sibuntuon Village. Then, my gratitude is also conveyed to the people of Sibuntuon Village who have helped a lot with this KPPM activity.